Estimation of arsenic contents in rice purchased on Peruvian markets and estimation of dietary intake by Peruvians through rice consumption - Zhunaula Guaman, Sonia Tatiana (2021)
Rice (Oryza sativa L) is an important source of essential elements but also can contain high As concentrations, which may be consumed and causes health effects. This work aimed to contribute to the lack of information quantifying the total arsenic (tAs) in 31 domestic rice (white rice, n=19; brown rice, n=7; parboiled rice, n=5) of different brands purchased in Peruvian markets. The tAs content was conducted by ICP-MS. The tAs concentration was compared to the maximum limits prescribed by regulatory agencies. Dietary intake (DI), dietary exposure (DE), and margin of exposure (MOE) were estimated. tAs concentration in white, brown and parboiled rice were 0.292 ± 0.106 mg/kg, 0.401 ± 0.081 mg/kg, 0.229 ± 0.03 mg/kg, respectively. Arsenic concentration in white rice exceeded limits recommended by FAO/WHO (0.20 mg kg-1), and European legislation (0.25 mg kg-1), but no Mercosul limits (0.3 mg kg-1). The DE showed that, on average, Peruvians consume 5.60 μg As kg-1 BW weekly. The MOE value was higher than 1 at the mean dietary exposure level. Our findings suggest that the health risk from dietary arsenic exposure is low for the Peruvian population. However, more studies are needed to reduce dietary arsenic exposure in Peru.